EVALUASI BRAND POSITIONING DAN PENGEMBANGAN BRAND STRATEGY RSKB JATIWINANGUN PURWOKERTO SEBAGAI RUMAH SAKIT KHUSUS BEDAH - , Lindasari Santosa; , Ario Setra Setiadi, Ph.D.DipM., ACIM ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Hospital industry in Indonesia is very competitive not only in the number of hospitals but also in terms of variations of services. Having understanding, implementing brand positioning and the right brand strategy for RSKB Jatiwinangun Purwokerto are a must for their marketing strategy to win the competition and to anticipate the need of demanded patients. Estabslihing brand positioning for RSKB Jatiwinangun Purwokerto will enhance its competitiveness, customer satisfaction, and improve employee performance. Objective: This study is to evaluate the brand positioning that inherent in RSKB Jatiwinangun Purwokerto based on the perceptions of internal and external customers and develop brand strategy to change the dominance of the personal doctor positioning to brand RSKB Jatiwinangun Purwokerto as a hospital specialized in surgical. Method: This study uses descriptive case studies methods, where surveys are used then continued with the focus group discussions with senior management and shareholders of RSKB Jatiwinangun Purwokerto. This study is to have in depth understanding hospital brand positioning strategies and determine selected. This approach is selected to obtain internal and external customer's perception toward variables on hospital brand. The process was followed by SWOT analysis to formulate brand strategy that can be used by RSKB Jatiwinangun Purwokerto. Result and discussion: The study was conducted on 196 respondends.They are 50 in patients, 50 out patients, 50 visitors, and 46 employees RSKB Jatiwinangun. The result shows that the respondents have a positive perception on the positioning of doctors, medical equipment technology, nursing, hospital performance, and positioning of RSKB Jatiwinangun Purwokerto as a whole. Base on the analysis from questionnaires result and focused discussion, we found that there is significant influence of respondents' perceptions to the brand positioning RSKB Jatiwinangun Purwokerto. The study revealed that the positioning would be, whether the hospital is better known as a general hospital or surgical hospital, middle class hospital or upper-class one and whether brand hospital is stronger than a doctor positioning. Management of RSKB Jatiwinangun Purwokerto should understand that the employee is a "living brand". Employees can strengthen or weaken the reputation of the company through any singleb service they delivered and can encourage the promotion through good word of mouths (external brand communications). By focusing on the needs of patients, RSKB Jatiwinangun Purwokerto can build a strong brand in health services in Banyumas and nearby area, supported with word of mouths promotion and other means of simple promotions. The analysis show as well that RSKB Jatiwinangun Purwokerto is not a leader in Banyumas or Purwokerto area. One of the reason is because they do not have specialist in service that can differentiate it from other hospitals. RSKB Jatiwinangun should have the services of aesthetic plastic surgery and reconstruction. In the product life cycle, RSKB Jatiwinangun Purwokerto is at introduction stage. RSKB Jatiwinangun Purwokerto need to be cautious in developing the strategy. Strategic planning, especially on brand strategy has to be able to bring them to development stage. Today, the focus is to promote its brand name - RSKB Jatiwinangun Purwokerto. Logo, slogan and brand story will follow later. By continuesly promoting brand name - RSKB Jatiwinangun Purwokerto - it will gradually overcome personal doctor positioning. Conclusion and recommendation: Based on descriptive case studies methods, the result concludes that perception of outpatients, inpatients, visitors and employees on the brand image of RSKB Jatiwinangun Purwokerto is positive. Brand positioning strategy of RSKB Jatiwinangun Purwokerto can be used to trasform people's perception on personal doctor positioning to hospital brand. RSKB Jatiwinangun Purwokerto will remain its specialty as surgical hospitals, provide general services to the community with a sizable portion and having plastic surgery services. To maximize the benefits of brand positioning RSKB Jatiwinangun Purwokerto, word of mouths promotion has to be driven together with other mean of promotions that are simple and easy to understand by customers. Level of capabilities among nurses in medical and communication should be equal, similarry for doctors